HERITAGE OF ACADEMICIAN N.V. TSITSIN: STATE-OF-THE-ART AND POTENTIAL OF THE COLLECTION OF INTERMEDIATE WHEAT × COUCH-GRASS HYBRIDS - V. P. Upelniek; V. I. Belov; I. P. Ivanova; S. P. Dolgova; A. S. Demidov (Вавиловский журнал генетики и селекции)
The work overviews the state, achievements, and prospects of the collection of perennial and ratooning intermediate wheat × couch-grass hybrids (2n = 56) kept in the N.V. Tsitsin Main Botanical Garden. It demonstrates the superiority of new forms in biological and economically significant parameters over hybrids obtained during the research activity of Аcademician N.V. Tsitsin. Stable genotypes with good performance in the degree of overwintering for 2–3 years of life were selected. Accessions promising in terms of yield, high protein content in grains, good baking qualities, fresh yield for three mowings, and pest resistance were chosen. Data on the biodiversity of botanical varieties of the Triticum agropyrotriticum Cicin species, gliadin polymorphism, and genome in situ hybridization are provided.